Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jce.14973
|View full text |Cite
|
Sign up to set email alerts
|

Ablation Index‐guided high‐power (50 W) short‐duration for left atrial anterior and roofline ablation: Feasibility, procedural data, and lesion analysis (AI High‐Power Linear Ablation)

Abstract: Objectives To evaluate the feasibility, procedural data, and lesion characteristics of the anterior line (AL) and roofline (RL) ablation by using ablation index (AI)‐guided high power (50 W) among patients with recurrent atrial fibrillation (AF) or atrial tachycardia (AT) after pulmonary vein isolation (PVI). Methods Data from 35 consecutive patients with macro‐reentrant left atrial tachycardia or substrate at the left atrium anterior wall or roof after previous PVI were collected. Ablation power was set to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
(30 reference statements)
0
16
1
Order By: Relevance
“…At present, there is no consensus in definition for what constitutes HPSD ablation, which varied from 50 to 90 W. This variation is also reflected in lesion geometry [27]. Even if the focus of the recent study from Zanchi et al centred on acute ablation success, and the difference of the power setting was lower compared with our study, they could still show that AI-guided high-power (50 W) ablation, targeting AI 500, seems to be a feasible technique with high first pass block rate for anterior line ablation [28]. However, AI is not validated for HPSD and more clinical data are required for line ablation with HPSD, especially with regard to long-term results.…”
Section: Main Findingscontrasting
confidence: 58%
“…At present, there is no consensus in definition for what constitutes HPSD ablation, which varied from 50 to 90 W. This variation is also reflected in lesion geometry [27]. Even if the focus of the recent study from Zanchi et al centred on acute ablation success, and the difference of the power setting was lower compared with our study, they could still show that AI-guided high-power (50 W) ablation, targeting AI 500, seems to be a feasible technique with high first pass block rate for anterior line ablation [28]. However, AI is not validated for HPSD and more clinical data are required for line ablation with HPSD, especially with regard to long-term results.…”
Section: Main Findingscontrasting
confidence: 58%
“… 5 Feasibility and safety of the HSPD procedure has been previously demonstrated in several studies. 16 A study that included over 10,000 patients (Winkle and colleagues 2 ) showed that HPSD ablations had lower complication rates and shorter procedural times compared to other conventional methods. Leshem and colleagues 17 echoed this finding by demonstrating that HSPD actually improved lesion-to-lesion uniformity, linear contiguity, and transmurality compared to conventional ablation while maintaining a similar safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…It also results in less collateral damage to extra-cardiac structures due to reduced resistive heating (16). Feasibility and safety of the HSPD procedure has been previously demonstrated in several studies (17). In a study that included over 10,000 patients (Winkle et al), it showed that HPSD ablations had lower complication rates and shorter procedural times compared to other conventional methods (18).…”
Section: Relationship Of Power and Duration With Etimentioning
confidence: 94%
“…In a previous study, HP-SD artificial intelligence-guided ablation at a maximum of 50 W was evaluated [ 2 ]. The technique seemed to be safe and effective, but no real-time temperature surveillance was possible with conventional CF sensing catheters.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter ablation has proven to be a very successful procedure for patients with atrial fibrillation (AF), with excellent outcomes on long-term follow-up. Recently, a radiofrequency (RF)-based, power-controlled ablation mode called high-power, short-duration (HP-SD) has been introduced that delivers a maximum of 50 W for treatment with pulmonary vein isolation (PVI) and deployment of linear lesions [ 1 , 2 ] With HP-SD, the length of the procedure and RF time are shorter and rates of isolation on the first past are increased, compared with standard RF ablation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%